Distress in Emerging Adults: Further Evaluation of the Painful Feelings About Divorce Scale. Issue 2 (17th February 2019) - Shanholtz, Caroline E.; Brown, Sacha Devine; Davidson, Ryan D.; Beck, Connie J.
ABSTRACT: Young adults from divorced families experience clear emotional distress despite most not meeting diagnostic criteria for emotional disorders. Laumann-Billings and Emery (2000) developed the Painful Feelings About Divorce (PFAD) scale to assess the emotional distress emerging adults feel regarding childhood parental divorce. The study sample is undergraduates predominately between the ages of 18 and 22. This study adds to the literature by (a) further demonstrating the PFAD scale reliability and validity, (b) including participants with both divorced and separated but never married parents, and (c) assessing generalizability of the PFAD with a more diverse socioeconomic sample.